Application of digital technologies: the case of virtual Masses - Hidalgo-Díaz, Pedro (2024)
In times of adversity, such as the recent COVID-19 pandemic, the bishops and priests of the Peruvian Catholic Church took on the task of transmitting Masses through digital environments. The aim of this study is to measure the reception that the transmission of the “virtual” Mass reached among the Catholic faithful of Lima and the evaluation of this experience. Its approach was quantitative with a correlational design. The online questionnaire “Experience of the Mass during the pandemic” was applied to identify the way in which 836 Catholic faithful from Lima have lived the experience of the transmission of “virtual” Masses. The findings showed that the use of technology and virtual media for religious practice is valued differently, with women being more religious than men. It was observed that young people have a greater understanding of the inequality between “face-to-face Mass” and “virtual Mass”.